Optimising water storage for climate resilience: geospatial targeting for small tanks rejuvenation in Sri Lanka - Lopane, F. D.; Ayling, S.; Hoo, Y. R.; Shamsudduha, M.; Wang, Q.; Joseph, G.; Bahuguna, A. (Elsevier, 2025)
In Sri Lanka, climate change and recurrent droughts pose significant threats to agricultural communities. Village water storage tanks have been used in countries in South Asia since the third millennium BC. According to the National Tanks Survey, Sri Lanka has some 23,000 small tanks of 80 ha or less; however, 21 percent are currently non-functional due to decades of neglect. This study designs a National Prioritisation Index for the rejuvenation of small tanks, employing a geospatial approach. Our research disaggregates district-level statistics at a 1 km resolution to map the demand from agricultural-dependent populations. We then construct several prioritisation indices that evaluate tanks from supply, demand, and utility for groundwater rejuvenation perspectives. Our findings highlight priority areas for tank rejuvenation concentrated in Kurunegala and Anuradhapura districts. The indices developed in this study provide a framework for targeting investments effectively, thereby optimising resource allocation for drought mitigation efforts. The approach can support enhancement of water security and resilience in vulnerable agricultural communities across Sri Lanka and in other parts of South Asia which are reliant on such infrastructure for water storage.